Factors Associated with Medication Compliance among Older Patients under the Care of Multidisciplinary Team in Geriatric Clinic at Lampang Hospital - ผลประสิทธิโต ศุภิสรา; ประคองยศ ชนินท์ (Journal of Health Science of Thailand, 2024)
Lampang Hospital established a geriatric clinic for elderly care by a multidisciplinary team. Most older people have chronic diseases that require medication for treatment. Compliance is therefore important for achieving treatment goals. This study aimed to investigate the prevalence and factors associated with medication compliance among older patients at the Geriatric Clinic in Lampang Hospital. It was conducted as a cross-sectional analytical study. Data were collected from medical records of older people who received care at the Geriatric Clinic in Lampang Hospital on a single occasion from June 2018 to December 2020. The data collected included baseline characteristics and medication compliance. The baseline characteristics were analyzed by descriptive statistics; and the factors associated with medication compliance were evaluated using the Fisher exact test and multiple logistic regression. A total of 433 older people visited the geriatric clinic 1,364 times in this study. The median follow-up time was 2 (IQR: 1,4) times. The mean age of patients was 79.3 (SD=8.3) years. Good medication compliance was at 75.1%. The following factors were associated with medication compliance: the elderly with a caregiver for drug use were 1.49 times more likely to have good medication compliance (ORadj=1.49; 95% CI: 1.03-2.17). The elderly with heart disease were 1.68 times more likely to have good medication compliance (ORadj=1.68; 95% CI: 1.02-2.76). But elderly with diabetic disease had lower medication compliance than 0.56 times (ORadj=0.56; 95% CI: 0.38-0.82); and the elderly with asthma and chronic obstructive pulmonary disease had less medication compliance than 0.27 times (ORadj=0.27; 95% CI: 0.16-0.45). There should be a procedure to take care of the elderly, especially those who do not have a caregiver for supporting medical use, people with diabetes mellitus, asthma or chronic obstructive pulmonary disease, to increase medication compliance and help the elderly achieve their treatment goals.